Shrub-induced snowpack variability alters wintertime soil respiration across a simulated tundra landscape. Issue 1 (1st January 2018) - Ackerman, Daniel
ABSTRACT: Across the arctic tundra, the expansion of tall shrubs is expected to alter soil microbial activity in winter through shrub effects on snow redistribution. Tall shrubs act as a windbreak, trapping deep snowdrifts that insulate the ground from extreme cold and elevate soil respiration within shrub patches. However, this windbreak effect may reduce both snow cover and soil respiration in open tundra areas outside shrub patches. The net impact of increasing shrub cover on soil respiration across landscapes with heterogeneous vegetation cover and snow depths remains unknown. Here, I use a set of tundra landscape simulations to address this knowledge gap. The simulations vary shrub cover, mean snow depth and the strength of shrub windbreak effect. I show that for mean snowfall depths 40 cm or greater, increasing shrub cover usually reduced landscape-level soil respiration due to greater heterogeneity in snow depth. These simulations suggest that there is no overarching positive relationship between shrub density and wintertime soil respiration on a landscape scale. Hypotheses generated from these simulations may be tested empirically to improve the representation of tundra vegetation and snow dynamics in Earth System Models.